A quantitative evaluation of water resource management policies in China based on the PMC index model - Nina Wang; Wenbin Wang; Tao Song; Huanming Wang; Zhe Cheng (Water Policy, 2022)
Water policies play a critical role in good water governance and sustainable water development. The evaluation of water policies helps improve the quality of water policy systems and water governance. This study quantitatively evaluated water resource management policies through the policy modeling consistency (PMC) index model and a text-mining method based on national water resource management policy texts produced from 2011 to 2019. This study constructed an evaluation index system based on the water resource management policy's high-frequency words, including 9 first-level variables and 43 second-level variables; furthermore, it compared and analyzed key water resource policies based on the PMC index and PMC surface. The results showed that China's water resource management policies are generally applicable, but it needs to be improved. China's water resource management policies are reasonable in terms of policy nature, policy function, policy priority, and function level, and need to be further improved in terms of policy prescriptions, incentive constraints, policy fields, policy evaluations, and policy priorities. This study thus provided a scientific basis for the optimization of water resource management policies and water governance capacities in China. HIGHLIGHTS The key water resource management policies in China have been evaluated through the hybrid method that includes PMC model, text mining, and content analysis.; An evaluation index system has been constructed based on the high-frequency words of policy texts, including 9 first-level variables and 43 second-level variables.; This study compared and analyzed key water resource policies based on the PMC index and PMC surface.;